Folate Receptor-Alpha Targeted 7x19 CAR-γδT Suppressed Triple-Negative Breast Cancer Xenograft Model in Mice. (7th March 2022) - Ye, Xueshuai; Deng, Xinna; Wen, Junye; Li, Yang; Zhang, Mengya; Cai, Ziqi; Liu, Guan; Wang, Hezhi; Cai, Jianhui
Abstract : Background . Triple-negative breast cancer (TNBC) is the worst prognosis subtype of breast cancer due to lack of specific targets. Recent studies have shown that immunotherapy may solve that problem by targeting folate receptor-alpha (FR α ). Methods . Gene modified γδ T cells were manufactured to express FRa specific chimeric antigen receptor (FRa CAR) and secrete interleukin-7 (IL-7) and chemokine C–C motif ligand 19 (CCL19). CAR- γδ T cells that secrete IL-7 and CCL19 (7 × 19 CAR- γδ T) were evaluated for their antitumor activity both in vitro and in vivo. Results . 7 × 19 CAR- γδ T showed remarkable antitumor activity in vitro. Combined with PBMC, 7 × 19 CAR- γδ T inhibited TNBC xenograft model growth superiorly compared with single-application or conventional CAR- γδ T cells. Histopathological analyses showed increased DC or T cells infiltration to tumor tissues. Conclusion . Taken together, our results showed that 7 × 19 CAR- γδ T have remarkable anti-TNBC tumor activity and showed a broad application prospect in the treatment of incurable TNBC patients.